2005
DOI: 10.1021/jf0519360
|View full text |Cite
|
Sign up to set email alerts
|

Self-Diffusion Coefficient of Water in Tofu Determined by Pulsed Field Gradient Nuclear Magnetic Resonance

Abstract: The self-diffusion coefficient of water in soybean protein dispersion and tofu was measured by pulsed field gradient (PFG) NMR. A soy protein isolate (SPI) dispersion (6 and 12%, w/w) in water, calcium cross-linked precipitate, and tofu were used for comparison. The self-diffusion coefficient of water (D) in the SPI dispersion, 2.23 x 10(-9) m2/s, was estimated lower than that of free water, 2.6 x 10(-9) m2/s at 25 degrees C, and decreased as the SPI concentration increased. It further decreased by the additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…The surface diffusion constant (D) for DOPC in bilayers is reported as 3 · 10 À8 cm 2 s À1 [36]. The surface diffusion constant of water molecules is three orders of magnitude faster at $2 · 10 À5 cm 2 s À1 [37]. It therefore can be argued that the Debye element in the complex capacitance plots in Fig.…”
Section: Modelmentioning
confidence: 98%
“…The surface diffusion constant (D) for DOPC in bilayers is reported as 3 · 10 À8 cm 2 s À1 [36]. The surface diffusion constant of water molecules is three orders of magnitude faster at $2 · 10 À5 cm 2 s À1 [37]. It therefore can be argued that the Debye element in the complex capacitance plots in Fig.…”
Section: Modelmentioning
confidence: 98%
“…28 The low-temperature activation energies of water dynamics in these models 28 are, however, about a factor of 3 larger than the value of 0.14 eV reported in early QENS work. 6 Static field gradient (SFG) and pulsed field gradient (PFG) NMR proved a versatile tool to investigate the translational diffusion of water on length scales of about 10 −8 -10 −5 m. 33 The potential of this method was exploited to determine self-diffusion coefficients D of water in protein matrices, 7, 34-37 in nano-and mesoporous solids, [38][39][40][41] in food matrices, [42][43][44][45][46] in hydrogels, 47 and in construction materials. 48,49 For the water diffusion in lysozyme, a crossover in the temperature-dependent diffusivity D(T) in the vicinity of 225 K was taken as evidence that a FS transition of the water results in a loss of flexibility of the protein.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the exchange lifetime of the proton on the micelle surface was estimated to be about 8.0 ms, based on the longitudinal magnetization decay with the spin-lattice relaxation time (T 1 ). On the other hand, Hong and Lee (2006) reported that restricted diffusion of hydrated water and proton exchange were not observed on the surface layer of pores formed in the protein network of tofu, indicating a hydration effect through water-protein interactions, even with 8.6 T/m of gradient strength and 5.0 ms of diffusion time, due to the absence of barriers for diffusion and the fast proton exchange on the surface.…”
Section: Ricementioning
confidence: 97%
“…According to our previous studies, the effective self-diffusion coefficient of water and the cellular membrane permeability in yeast and chlorella were also successfully calculated (Cho et al, 2003;Suh et al, 2003), and the changes in the cellular membrane permeability of water were observed in yeast cells harvested at different growth stages and treated with different heating methods (Hong et al, 2004). The effective self-diffusion coefficient and restricted diffusion could be distinguished from diffusion according to the obstruction effect induced by the impenetrable slow-moving polymer molecules and the hydration effect through water-protein interactions on the surface layer of pores formed in the protein network of tofu (Hong & Lee, 2006).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation